2015
DOI: 10.4103/0259-1162.156299
|View full text |Cite
|
Sign up to set email alerts
|

A study to compare the overall effectiveness between midazolam and dexmedetomidine during monitored anesthesia care: A randomized prospective study

Abstract: Background:Monitored anesthesia care (MAC) combines intravenous sedation along with local anesthetic infiltration or nerve block. Several drugs have been used for MAC, but all are associated with complications. Dexmedetomidine is a selective α2-adrenoceptor agonist with both sedative and analgesic properties and is devoid of respiratory depressant effects. Its short elimination half-life makes it an attractive agent for sedation during MAC.Aim:Comparative evaluation of dexmedetomidine and midazolam for MAC.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Most of the studies reported a statistically significant higher physician satisfaction with DEX (n = 15; 42.8%), when compared to the control group, 61 , 65 , 30 , 71 , 36 , 98 , 43 , 52 , 63 , 73 , 58 , 18 , 97 , 37 , 94 or did not report any statistically significant difference between both groups (n = 15; 42.8%). 23 , 81 , 69 , 38 , 44 , 56 , 104 , 54 , 35 , 53 , 29 , 72 , 39 , 75 , 47 A few studies (n = 6; 10.9%) reported a statistically significant higher physician satisfaction in favor of the control group.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Most of the studies reported a statistically significant higher physician satisfaction with DEX (n = 15; 42.8%), when compared to the control group, 61 , 65 , 30 , 71 , 36 , 98 , 43 , 52 , 63 , 73 , 58 , 18 , 97 , 37 , 94 or did not report any statistically significant difference between both groups (n = 15; 42.8%). 23 , 81 , 69 , 38 , 44 , 56 , 104 , 54 , 35 , 53 , 29 , 72 , 39 , 75 , 47 A few studies (n = 6; 10.9%) reported a statistically significant higher physician satisfaction in favor of the control group.…”
Section: Resultsmentioning
confidence: 97%
“… Nooh 15 Saudi Arabia (20–28) 56 18 1 Surgical removal of the third molar NIBP, ECG, pulse oximeter, modified OAA/S score and BIS 1: 1.5 μg.kg −1 intranasal atomized DEX 2: intranasal water 30 min before the procedure No clear definition Preoperative anxiety, reaction to the anesthetic injection, pain, sedation score, vital signs, adverse events and complications and total analgesic consumption. Dental procedure (n = 19) Rasheed 30 India (20–50) 46 50 1, 2 Not specified NIBP, ECG, pulse oximeter and OAA/S score 1: 1 μg.kg −1 iv DEX for 2 min + 0.5 mg.kg −1 iv ketamine 2: 0.05 mg.kg −1 iv MDZ for 2 min + 0.5 mg.kg −1 iv ketamine NR No clear definition Duration of procedure, induction-incision time, hemodynamic effects, duration of analgesia, mean a total extra dose of ketamine and patient and physician satisfaction. Salazar 31 Venezuela (18–30) 38.6 44 1, 2 Surgical removal of the third molar RR, SBP, DBP, MAP, SpO 2 , ECG, HR and RSS 1: 0.2 μg.kg −1 .h −1 iv infusion DEX 2: 0.1 mg.kg −1 .min −1 iv infusion propofol Before and during the procedure Patient behavior (pain or discomfort) during the procedure Sedation score, time until sedation, patient response, hemodynamic and respiratory effects, need for additional anesthetic, recovery time, need for rescue Alfentanil and adverse events and complications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Another study reported that sedation with dexmedetomidine for MAC is associated with lower rescue doses of sedatives and analgesics as well as it is associated with higher surgeons and patient satisfaction score as compared to midazolam. 21 Parikh and colleagues compared the effects of dexmedetomidine to the standard midazolam-fentanyl combination in patients undergoing tympanoplasty surgery under MAC. It boosted patient and surgeon satisfaction, indicating a better sedative profile; however, it decreased heart rate and blood pressure, needing regular monitoring.…”
Section: Resultsmentioning
confidence: 99%